DODOL SICINI FORMULATION WITH EUCHEUMA COTTONII SEAWEED FORTIFICATION - A Virati Syamda; Tri Widayati Putri; Awaluddin Awaluddin (Universitas Mataram, 2024)
Dodol, which belongs to the category of semi-moist foods (foods with intermediate moisture), is immediately consumed due to its sugary, chewy appearance. Seaweed will acquire economic value subsequent to undergoing additional processing, such as the transformation into seaweed dodol. The objective of this study is to differentiate the nutritional and hedonic benefits of Sicini dodol in response to fortification with Eucheuma cottonii seaweed. GOWATE REGION-PERI. This research methodology employs three interventions and three repetitions in an experimental laboratory. Analysis of data employs the Anova test. The water contents of samples A (27.81%), B (35.86%), and C (36.86%) were displayed in the results. Ashes A (1.04%), B (1.40%), and C (1.64%) by weight. The protein concentrations are as follows: A (3.44%), B (3.48%), and C (3.58%). Samples A (7.27%), B (9.26%), and C (8.86%) contained fat, respectively. Carbohydrates A (56.60%), B (61.69%), and C (66.02%) are examples. Samples A (1.61%), B (3.73%), and C (6.32%) comprise crude fiber. The hedonic test outcomes indicate that samples A (7.50), B (6.80), and C (6.20) have an average appearance. As indicated by the average fragrance of samples A (7.27), B (6.70), and C (5.40). Based on the typical taste, samples A (7.50), B (7.10), and C (5.70) are evident. As shown by the average textures of samples A (7.00), B (6.40), and C (5.60). In conclusion, seaweed lunkhead Eucheuma cottonii affects chemical and hedonic quality. Keywords: Dodol, Eucheuma cottonii seaweed, chemical tests, hedonic